2020
DOI: 10.1080/23802359.2020.1748537
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the Garra tibetana (Cypriniformes: Cyprinidae)

Abstract: The Garra tibetana, an important economic fish belonging to the genus Garra, family Cyprinidae, is mainly distributed in Tibet with rare biological resources. Here, we sequenced and characterized the complete mitochondrial genome of G. tibetana for the first time, and the results showed that the total length of G. tibetana mitogenome was 16,861 bp, consisting of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and 2 control regions. Unlike the typical mitochondrial genome organization in vertebrate, the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…They feed on plant debris in open-water habitats and on periphyton in bottom-surface habitats ( Kullander and Fang, 2004 ; Nebeshwar et al, 2009 ). Currently, 20 different Garra species have been identified from the Brahmaputra River basin, three of which in China, namely, G. dengba , G. Tibetan , and G. yajiangensis caught our attention due to the rearrangement in their mitochondrial genome ( Deng et al, 2018 ; Gong, 2018 ; Gong et al, 2018 ; Zhang et al, 2020 ). They were all collected from high altitudes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They feed on plant debris in open-water habitats and on periphyton in bottom-surface habitats ( Kullander and Fang, 2004 ; Nebeshwar et al, 2009 ). Currently, 20 different Garra species have been identified from the Brahmaputra River basin, three of which in China, namely, G. dengba , G. Tibetan , and G. yajiangensis caught our attention due to the rearrangement in their mitochondrial genome ( Deng et al, 2018 ; Gong, 2018 ; Gong et al, 2018 ; Zhang et al, 2020 ). They were all collected from high altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…G. yajiangensis , a member of the long-nosed species group, is distinguished from other members of the group mainly by the presence of a prominent, quadrangular, slightly bilobed proboscis. Apart from G. tibetana has been reported as a complete mitochondrial sequence, current researches on these three Garra fishes are mainly stagnant in morphology while their corresponding molecular evolutions are still limited ( Zhang et al, 2020 ). In addition, Zhang et al (2020) identified two control regions in the mitochondrial genome of G. tibetana ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation